Alcoholic imaginaries in Pablo Neruda and Pablo de Rokha: towards a poetic of drunkenness (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
In this article, I analyze the alcoholic imaginaries elaborated in Oda al vino by Pablo Neruda and Borrachos dionisíacos by Pablo de Rokha. As a hypothesis, I propose that both texts are a defense or apology of alcohol and drunkenness, where the worth of alcohol consumption is closely connected with the idea of masculinity postulated by poetic voices. In this sense, I also propose that both texts configure a poetic of drunkenness, which belongs to the tradition of poets who have sung the virtues of alcohol and its effects from Antiquity to Modernity.
Keywords: Chilean poetry; Alcoholic imaginaries; Neruda; De Rokha